2015
DOI: 10.1371/journal.pone.0132642
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Deletion of an “ORFanage” Region Facilitates Host Adaptation in a “Photosynthetic” Cyanophage

Abstract: Viruses have been suggested to be the largest source of genetic diversity on Earth. Genome sequencing and metagenomic surveys reveal that novel genes with unknown functions are abundant in viral genomes. Yet few observations exist for the processes and frequency by which these genes are gained and lost. The surface waters of marine environments are dominated by marine picocyanobacteria and their co-existing viruses (cyanophages). Recent genome sequencing of cyanophages has revealed a vast array of genes that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…WH7803 was grown in ASW medium in continuous light (25)(26)(27)(28)(29)(30) mmol photons m À2 s À1 ) at 23 C to an OD 750 nm between 0.35 and 0.40. Cell concentrations were measured using flow cytometry (FACScan, Becton Dickinson) and diluted to a concentration of 1 3 10 8 cells/ml with fresh ASW medium [44].…”
Section: Experimental Procedures Infection Conditionsmentioning
confidence: 99%
“…WH7803 was grown in ASW medium in continuous light (25)(26)(27)(28)(29)(30) mmol photons m À2 s À1 ) at 23 C to an OD 750 nm between 0.35 and 0.40. Cell concentrations were measured using flow cytometry (FACScan, Becton Dickinson) and diluted to a concentration of 1 3 10 8 cells/ml with fresh ASW medium [44].…”
Section: Experimental Procedures Infection Conditionsmentioning
confidence: 99%
“…Previously, it was suggested that these unique genes probably encode specific enzymes or proteins for the cyanophage life cycle [43,44]. However, comparative genomic analyses have demonstrated that the majority of them show high similarity with cellular homologues of host cyanobacterial origin at the DNA sequence level [45,46]. There are many studies showing evidence of cyanophage acquisition of host genes encoding proteins or enzymes in key metabolic processes [47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…This phage is probably a result of a low-level contaminant in the stock of S-PM2d that was only detected due to the very high depth of initial sequencing coverage (> 2,000×). This contaminant has not been detected previously in S-PM2d which was recently purified by three rounds of plaque assay and sequenced to a high depth of coverage ( Puxty et al, 2015 ).…”
Section: Resultsmentioning
confidence: 97%
“…The dearth of reference phage genomes infecting cells of a particular genera is highlighted by the estimation of 5,476 viral populations in the upper oceans, of which only 39 could be affiliated to cultured viruses ( Brum et al, 2015 ). Re-sequencing of cultured phage genomes also provides insight into their genome evolution ( Puxty et al, 2015 ). Altogether, it is clear that there exists a developing need for a high-throughput approach to the sequencing and re-sequencing of cultured phage genomes.…”
Section: Introductionmentioning
confidence: 99%